Crenças de uma formadora de professores de língua inglesa e reflexões de seus alunos sobre o papel do bom formador - Borges, Tatiana Diello (2017)
This research was carried out in a Modern Language Course at a federal university in central western Brazil and aimed at investigating the beliefs of an English language teacher educator about what it means to be a good English language teacher educator in the process of teaching and learning, and also at verifying the reflections of the English language teacher educator’s students, pre-service English teachers, about her beliefs. The theoretical framework was based on the field of language teachers’ education (PERRENOUD, 1999; CELANI, 2001, 2003; ALARCÃO, 2002, 2011; MATEUS, 2002; VIEIRA-ABRAHÃO, 2002; ARAÚJO, 2004; MIZUKAMI, 2005; OLIVEIRA, 2008; MAZZA; ALVAREZ, 2011; NASCIMENTO, 2011; VIANA, 2011; HALU, 2014) and beliefs about foreign language teaching/learning (PAJARES, 1992; GIMENEZ, 1994; JOHNSON, 1994; BARCELOS, 1995; HORWITZ, 1999; SILVA, 2005; SOARES; BEJARANO, 2008; PERINE, 2012; MARQUES DE OLIVEIRA, 2013; HAYASHI, 2015). The case study methodology was employed and the following data collection instruments were used: questionnaires, narrative, interviews, class observations (supported by field notes and audio recordings), and group discussion. Regarding the teacher educator’s beliefs, results suggest that she believes that the good teacher educator makes use of pair/group work, employs ludic activities in classes, values continuous education, uses technological resources, works not only with intellectuality, but also with emotions/feelings, and can influence the adoption of postures throughout pre-service teacher’s academic education and teaching practice. The data obtained also reveal the existence of a central belief in which the other beliefs of the English language teacher educator are held: the good teacher educator must pay careful attention to the learning environment so that the learner can feel comfortable to learn. It is also verified that there is congruence between the teacher educator’s beliefs and her pedagogical actions. As for the reflections of students, pre-service teachers, concerning their teacher educator’s beliefs, results indicate that they share her beliefs and understand that they influence in a positive way both their academic education and teaching practices, since they already work as English language teachers. The analysis of the students’ reflections also suggests that the teacher educator’s central belief - the good teacher educator must pay careful attention to the learning environment so that the learner can feel comfortable to learn - seems to be understood in a positive way by the students, once they demonstrate a more humanized posture because they acknowledge that the learners’ emotional framework must be taken into consideration. This study indicates the importance of seriously considering the possibility of teacher educator’s influence in relation to their undergraduate students. It is imperative to keep this in mind when dealing with teachers’ education, since teacher educator’s beliefs and actions can influence both positively and negatively.